Pleomorphic Adenoma of the Palate in a 10-year-old Child: A Case Report - SH Tabatabaei; L Maleki; H Mirshamsi; AR Navabazam (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2016)
Salivary gland tumors  are  uncommon  within  children and  when  they do arise,  they  mainly  affect  the  major  salivary glands. Minor salivary gland  tumors  are  rare  in  children, which are  responsible for less than 10% of all the cases. Pleomorphic adenoma is the most common tumor of  the salivary glands in the all ages. A 10-year-old boy referred to the dentistry clinic with a swelling in the palate of adjacent unerupted right maxillary second molar. In sampling by curettage, clinical pathologist reported ameloblastoma. The patient was referred to the dental school of Shahid Sadoughi University of Medical Sciences for consultation. Second  microscopic analysis showed a benign pleomorphic adenoma that was confirmed by special staining periodic acid-Schiff (PAS), immunohistochemistry cytokeratin(CK), and S100 staining. Pleomorphic adenoma of minor salivary gland of children should be considered as a differential diagnosis of intraoral swelling in the palate.